267 ENHANCED SUPEROXIDE ACTIVITY INDUCES SALT SENTSITIVITY IN ENDOGENOUS NITRIC OXIDE SYNTHASE KNOCKOUT MICE. Issue 1 (1st January 2007) - Hess, A.; Kopkan, L.; Castillo, A.; Majid, D. S.A.
Abstract : Nitric oxide (NO) synthase inhibition enhances superoxide (O2 − ) activity. The present study was conducted to examine the hypothesis that salt sensitivity is induced by superoxide (O2 − ) activity that is enhanced due to a deficiency in endogenous nitric oxide (NO) production. Male knockout (KO) mice lacking the gene for endothelial NO synthase and their genetic background wild-type C57BL6J mice (WT) were fed a diet containing either normal salt (NS, 0.4% NaCl) or high salt (HS, 4% NaCl) and treated with or without a O2 − scavenger, tempol (400 mg/L), in drinking water for 2 weeks. Systolic blood pressure (SBP) was measured by tail-cuff plethysmography and urine collection was performed in metabolic cages on every third day during the 2-week experimental period. Urinary 8-isoprostane concentration (a marker for oxidative stress) was measured by ELISA kit (Cayman). Baseline SBP values in KO groups were significantly higher compared with WT groups (138 ± 5 vs 116 ± 4 mm Hg). At the end of the 2-week period, there was no significant difference in SBP between the tempol-treated and untreated WT groups with NS intake. However, SBP was significantly lower in tempol-treated KO mice compared with untreated KO mice fed on NS diets (131 ± 2 vs 142 ± 3 mm Hg). HS intake had no effect on SBP in untreated and treated WT groups; however, SBP was significantly increased in KO with HS intake (154 ± 4 mm Hg) over the 2-week period. Tempol significantly attenuated the effect of HS on SBP in the KO group (139 ± 2 mm Hg). There were no differences in baseline urinary 8-isoprostane excretion (UISO V) between WT and KO mice. However, at the end of 2 weeks, compared with WT and KO with NS intake (2.2 ± 0.1 and 2.4 ± 0.3 ng/d, respectively), UISO V was increased in both WT and KO groups with HS intake (2.9 ± 0.3 and 3.6 ± 0.2 ng/d, respectively), the increase in UISO V being greater in KO compared with WT. Tempol attenuated UISO V in both WT and KO with HS intake (2.5 ± 0.1 and 2.9 ± 0.2 ng/d). These data suggest that, in the condition of eNOS enzyme deficiency, dietary high-salt intake induces enhanced O2 − activity that contributes to the development of salt-sensitive hypertension.